Kritik Nalar Islam Indonesia: Tinjauan Problematis Relevansi Teks dan Konteks - Wildan Hidayat (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
This paper specifically discussed about non-Muslim leadership in the Islam context, especially in Indonesia. This paper also discussed with the studied concepts of leadership in Islam (non-Muslim) and Islamic countries which are led by people with another religion (non-Islam). Not only to the extent of permissibility or non-indulgence of non-Muslim leadership in Islam, but it presented the opinions of the pros and cons of this case. Then it can be taken a formulative idea that can bring Moslem of Indonesia to come up from the stagnancy of unknowledgeable sektesentric pattern against the rejection non-Muslim leadership without any real solution for himself and the Muslim community. Especially if the concept became contextualized with an Indonesia country with a Muslim as majority.